Plant roots and spectroscopic methods – analyzing species, biomass and vitality - Rewald, Boris; Meinen, Catharina (Frontiers in Plant Science, 2013)
In order to understand plant functioning, plant community composition and terrestrial biogeochemistry it is decisive to study standing root biomass, (fine) root dynamics and interactions below ground. While most plant taxa can be identified by visual criteria above ground, roots show less distinctive features. Furthermore, root systems of neighbouring plants are rarely spatially segregated; thus, most soil horizons and samples hold roots of more than one species necessitating root sorting according to taxa. In the last decades, various approaches, ranging from anatomical and morphological analyses to differences in chemical composition and DNA sequencing were applied to discern species’ identity and biomass below ground. Among those methods, a variety of spectroscopic methods was used to detect differences in the chemical composition of roots. In this review, spectroscopic methods used to study root systems of herbaceous and woody species in excised samples or in situ will be discussed. In detail, techniques will be reviewed according to their usability to discern root taxa, to determine root vitality, and to quantify root biomass non-destructively or in soil cores holding mixtures of plant roots. In addition, spectroscopic methods which may be able to play an increasing role in future studies on root biomass and related traits are highlighted.